The Effect of Work Discipline on Work Productivity of Construction Employees - Situmorang, Raftonado; Indra, Andika Ade; Maharani, Ifani Dilla; Sari, Oryza Lhara (Universitas Sebelas Maret, 2022)
Abstract: Progress and developments in the world of construction have greatly spurred the growth and development of the construction services business, especially in Indonesia. When carrying out activities, companies need human resources to achieve company goals, namely work productivity. Work productivity is a measure of input and output as well as the role of labor in the company. The factor that affect work productivity is work discipline. Discipline is an attempt to comply with the applicable regulations in the company. Employees must pay attention to the part of work discipline, especially employee absenteeism. Because work discipline greatly affects employee productivity factors. That’s why this research was conducted to determine the effect of work discipline on work productivity with case study in PT. PP (Persero) TBK. EPC Division RDMP RU V Balikpapan Project. The method used in this research uses multiple linear regression analysis with SPSS 23.0, 21 indicators that affect project work productivity of PT. PP includes employee compliance with all company regulations, and at work can improve performance. This is supported by the t-count work discipline value of 2.155 and a significant value of less than 0.05 with values of 0.044.